A neural network analysis of the influence of strategic and relational motivation on acquisition of inter-organisational network ties in the Ghanaian automobile cluster. (2018) - Xuhua, Hu; Addai, Michael; Danso, Bertha Ada; Ocloo, Chosniel Elikem
The acquisition of inter-organisational network ties remains a functional pre-requisite in the survival of a business venture. We sought in this study, to explore the extent to which strategy-driven motivational factors and relational motivational factors significantly influence acquisition of inter-organisational network ties. Our data was procured from a sample of 150 managers and owners of small scale automobile firms recruited from an automobile cluster in Ghana. We adapted but modified a feed-forward neural network model where data propagate along the connections in the direction from the network inputs to the network outputs from the extant literature. Our results showed a complementary relationship between the effects of interactions that precede the development of cooperation among organisations and strategic forces which involve the deployment of a firm's core competencies. We proposed the need for automobile SMEs in Ghana to harness potential sources of competitive strength such as previous experience of working together with others.